Differential Expression Of Proteins During Poultry Kidney Development - DR. PARVATHALA KALYANI,; DR. RAGA SUDHA MEDICHERLA,; DR. VASILI ASHOK, (International Journal of Pharma and Bio Sciences, 2012)
Proteins have a critical role in regulating organogenesis. Different sets of proteins are required at different stages of development. The present study was undertaken to study differential expression of proteins during poultry kidney development. Metanephric kidneys were collected from 9th, 11th, 13th, 15th, 17th & 19th day embryos, day old chicks and adult fowls of Vanaraja breed. The kidney tissues were homogenized, centrifuged, the supernatants were collected and analyzed by SDS PAGE. Prominent differential protein expression was evident on visual examination of the gel picture. Six unique protein bands with molecular weights of 129kDa, 108kDa, 97kDa, 90kDa, 68kDa and a broad band of 20-43kDa are identified at specific ages in kidney tissue extracts. Differential expression profile of proteins revealed upregulation of most of the proteins upto 15th embryonic day. It can be concluded that poultry kidney grows upto 15th embryonic day after the metanephros is formed on 8th embryonic day.